Practice and Repetition in Second Language Learning: A Self-Study Experience from a pre-service ESL Language Teacher (Jóvenes en la Ciencia, 2021)
In language learning, the importance of practice and repetition is often forgotten. Frequently, language learners are not presented with a significant number of opportunities to repeat, and consequently, obtain an adequate command of lexical and grammatical elements of a second language. To conduct this study, Webb’s (2007) and Webb and Nation’s (2017) ideas concerning the effects of repetition in vocabulary learning were considered. This self-study research project will present the results of a longitudinal investigation carried out over eight months by a student in the BA in English language teaching at the University of Guanajuato. The student was enrolled in two German language learning classes and data were collected in a Sway portfolio, using reflective journal entries and visual evidence. The data analysis presents results showing that written practice and repetition of grammatical and lexical constituents of German contributed positively to the participant’s second language learning. Written practice may have had such a positive effect on the participant’s learning because this type of rehearsal promotes the activation of several mental processes (Field, 2003). Another relevant finding was that auditive repetition is essential in language learning and acquisition since it increases exposure to the target language; therefore, it promotes the effective retention of new information. This study has implications for language teaching and teachers, as